2018
DOI: 10.3899/jrheum.171287
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of Sexual Dysfunction in Female Patients with Rheumatoid Arthritis: Results of a Cross-sectional Study

Abstract: FSD apparently is highly prevalent in female patients with RA, affects all subdomains of sexual function, and is most likely underestimated in daily clinical practice. Of note, FSD could not be linked to disability or RA disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…The percentage of women with FSD was higher in the RA group (106/223, 47.5%) when compared with HCO (24/169, 14.2%). Detailed data on the association between FSD and RA have already been reported elsewhere 17…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of women with FSD was higher in the RA group (106/223, 47.5%) when compared with HCO (24/169, 14.2%). Detailed data on the association between FSD and RA have already been reported elsewhere 17…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization (WHO) recognizes sexual health as an essential part of general health and an important part of human well-being. 62 According to the International Classification of Functioning, Disability and Health (ICF), sexual health encompasses 2 areas: intimate relationships and sexual functions, both of which can be affected in patients with RA. 63 Sexual dysfunction is a common health conflict that affects up to 50% of the population and in most cases it can be correlated with age.…”
Section: Sexual Activitymentioning
confidence: 99%
“…Previous research has reported high prevalence of impaired sexual health among persons living with chronic diseases such as rheumatoid arthritis (RA) [5][6][7][8][9], fibromyalgia [10,11] and multiple sclerosis [12]. Sexual dysfunction is also reported to be higher among persons with RA compared with healthy control groups, and the main influencing factor is pain [13,14]. Restoux et al (2020) concluded, in a recent systematic review based on 50 quantitative and six qualitative studies, that sexual dysfunction is highly prevalent among both men and women with inflammatory arthritis, and called for increased clinician awareness of this impairment, so as to guide provision of tailored education and support [15].…”
Section: Introductionmentioning
confidence: 99%